Enhancing the Learning Experience through Spiritual Growth in the Merdeka Curriculum at Islamic Educational Institution - Misnatun Misnatun; Rohmatul Ummah (Indonesian Journal of Education and Social Studies, 2023)
The purpose of this study is to describe efforts to improve student learning experiences based on spiritual growth in the independent curriculum at MI Zainul Anwar. This research was conducted with a qualitative approach with a descriptive type. The data collection technique used was interviews with the Head of Madrasah, Deputy Head of Curriculum, and two subject teachers, as well as documentation. Data analysis was carried out through three interactive steps, namely: (1) data condensation; (2) data exposure; and (3) drawing conclusions and verification. Data validity with source triangulation process. The results of the study explained that P5 namely self-potential development, self-empowerment, self-understanding, self-improvement, and students' social roles as a process of spiritual growth in the independent curriculum to improve student learning experiences that are tailored to student needs and increase learning experiences that will not be achieved through exposure purely verbal. So that learning experience was obtained and obtained through various learning activities as mentioned above. The subject matter functions more as a tool (means) not a goal (ends). Spiritual growth which was used as an approach in this independent curriculum illustrates various activities that are not only based on religious values but also uphold the affective aspects that students should have.